Father’s Involvement during the Pregnancy and Child Birth Time in Nepal - Ghimire, Maya Nath (Nepal Journal of Multidisciplinary Research, 2021)
This study was conducted in two districts: Lamjung and Chitawan. All the respondents were 25 years and above fathers. The study collected data from face to face in–depth interviews. The findings show that almost respondents (fathers) care their pregnancy wives. Furthermore, 25-40 age group respondents care their pregnant wives more sensitively: they are aware of providing rest, not allowing carrying loads, supplying nutritious food, providing love and affection, go together for pregnancy checkup and regular help to solve their wives’ problems at pregnancy time.